Investigation of self - organisation in the Benard experiment based on micro-scale simulation - Kaya, Emre. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
Self-organisation is the phenomenon where in a dynamic system made of autonomous, yet interacting components a global macro-scale regularity observable by an outside observer spontaneously emerges. Rayleigh-B enard Convection is one of the most common examples of this phenomenon. In this thesis, the B enard experiment, which involves the self-organisation of convection cells, has been simulated at micro-scale, i.e. at molecular level, in order to investigate the dynamics underlying this self-organisation phenomenon at its most fundamental level. Molecular dynamics simulations of the proposed 2D micro-scale model have been conducted under di erent external conditions to observe the dynamic behaviour range of the system. An image processing algorithm based on curl of the velocity eld has been developed to automatically detect the presence or absence of convection cells and thus the type of the dynamic regime at hand. The 2D micro-scale model developed in this thesis sheds light on how the dynamic regime depends on external conditions and provides an answer to the original question of this study whether the emergence of macro-scale order can be detected from the micro-scale perspective of a single particle.
Keywords: Thermodynamics .; Heat -- Transmission.